MENANAMKAN NILAI-NILAI ISLAM TERHADAP ANAK-ANAK MELALUI KULIAH KERJA NYATA: SEBUAH PENGABDIAN MASYARAKAT - Yolanda, Legin; Mardlia, Banuajie Rizqy; Saputra, Andesta; Mawarni, Papat Nisa; Tasya, Mei; Andayani, Retno; Tri Mutiara, Zalela; Novitasari, Anggun; Revola, Yashori; Lusiana, Nadila (CV. Kalimasada Group, 2024)
This article discusses the implementation of Islamic values in the Real Work Lecture (KKN) activities held in Rena Panjang Village. This research aims to explore how students can instill Islamic values in their KKN activities and their impact on village communities. In this context, values such as honesty, responsibility, and social care are integrated in various activities, including educational programs The research method used involves direct observation, interviews between students and villagers, and analysis of documentation of KKN activities. The results of the study show that the implementation of Islamic values through KKN in Rena Panjang Village has a significant positive impact. Students have successfully applied Islamic teachings in concrete actions, strengthened social relationships, and improved the quality of life of rural communities. In addition, this activity also helps students in developing their character and understanding of Islamic teachings. This article concludes that the integration of Islamic values in KKN is an effective strategy to increase the social benefits of the program and recommends the application of similar models in other locations to achieve similar results.